A new nesting record for the jabiru in Costa Rica - Villarreal Orias, Johnny (1998)
I document the first nesting record of theJabiru (Jabiru mycteria) in "Los Guatuzos" forest floodplain, Alajuela province, Costa Rica. The active nest was located in March 1995 at 10°49'23.70"N and 84°47'23.20"W. The nest was 16m high in a 23m high silk-cotton tree (Ceiba pentandra) and contained three chicks. The zone is not protected and active lumbering is underway.